PENENTUAN KADAR KOLESTEROL DENGAN METODE KROMATOGRAFI GAS - Laila Khamsatul Muharrami (AGROINTEK, 2011)
The methods for quantitative determination of cholesterol in foods by chromatography determination Two types of lipid classes including free cholesterol and cholesterol ester exist in food. Total cholesterol is measured after chemical hydrolysis of cholesterol esters to free cholesterolPrior to instrumental analysis, cholesterol is extracted from the food sample and saponified. The amount of the food sample depends on the cholesterol content; a sample containing ∼1 mg of cholesterol is required for lipid extraction. Saponification hydrolyzes the carboxyl group attached to carbon in cholesterol and yields only free cholesterol in unsaponifiable matter. The unsaponifiable matter can be extracted by n-hexane, diethyl ether, or petroleum ether. In the present protocol, unsaponifiable matter is extracted using n-hexane. This protocol requires prior knowledge of GC  methodologies and adherence to instructions from the instrument’s manufacturer.